2010
DOI: 10.1038/nrrheum.2010.196
|View full text |Cite
|
Sign up to set email alerts
|

Role of proinflammatory cytokines in the pathophysiology of osteoarthritis

Abstract: Osteoarthritis (OA) is associated with cartilage destruction, subchondral bone remodeling and inflammation of the synovial membrane, although the etiology and pathogenesis underlying this debilitating disease are poorly understood. Secreted inflammatory molecules, such as proinflammatory cytokines, are among the critical mediators of the disturbed processes implicated in OA pathophysiology. Interleukin (IL)-1β and tumor necrosis factor (TNF), in particular, control the degeneration of articular cartilage matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
1,919
1
28

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,208 publications
(1,998 citation statements)
references
References 106 publications
50
1,919
1
28
Order By: Relevance
“…We did not find significant differences in the expression of Aggrecan , Mmp13 or Col X in miR‐146a‐deficient chondrocytes compared with WT control. However, following treatment with IL‐1β, a pro‐inflammatory cytokine that promotes catabolism in articular cartilage (Kapoor, Martel‐Pelletier, Lajeunesse, Pelletier & Fahmi, 2011), mRNA level of Mmp13 and Col X was significantly increased, while Aggrecan was decreased in miR‐146a‐deficient chondrocytes in comparison with WT chondrocytes (Figure 2g). This suggests that miR‐146a modulates chondrocyte anabolic and catabolic activities through affecting cytokine regulation of gene expression.…”
Section: Resultsmentioning
confidence: 98%
“…We did not find significant differences in the expression of Aggrecan , Mmp13 or Col X in miR‐146a‐deficient chondrocytes compared with WT control. However, following treatment with IL‐1β, a pro‐inflammatory cytokine that promotes catabolism in articular cartilage (Kapoor, Martel‐Pelletier, Lajeunesse, Pelletier & Fahmi, 2011), mRNA level of Mmp13 and Col X was significantly increased, while Aggrecan was decreased in miR‐146a‐deficient chondrocytes in comparison with WT chondrocytes (Figure 2g). This suggests that miR‐146a modulates chondrocyte anabolic and catabolic activities through affecting cytokine regulation of gene expression.…”
Section: Resultsmentioning
confidence: 98%
“…Many pro-inflammatory chemical mediators and pro-inflammatory cytokines are known to play critical roles in the pathogenesis of osteoarthritis [80]. Zerumbone has been investigated for potential curative effects in chemical-induced osteoarthritis in animal models.…”
Section: In Vivo Anti-cancer Effects Of Zerumbonementioning
confidence: 99%
“…Tumour necrosis factor (TNF)-α, a proinflammatory cytokine, plays an important role in local immune response to invading organisms by initiating a cascade of reactions that culminates into inflammatory response to eliminate the invading organisms [4]. Previous studies had found that levels of TNF-α were elevated in the synovial fluid, synovial membrane, subchondral bone and cartilage [5,6]. Therefore, TNF-α is considered to play an important role in the pathophysiology of OA [5].…”
Section: Introductionmentioning
confidence: 99%